Study on the F-U-BVF analytical model for sustainable food design: a case study of tofu - Liang, Yuehui; Han, Yan (Frontiers in Sustainable Food Systems, 2024)
The food lifestyle has evolved from the regional differences that were previously shaped by different geographic locations to the pluralistic complexity of food styles that are now influenced by different user consciousnesses. The field of food design has assumed a greater social responsibility, while also facing the challenge of sustainable development. Consequently, it is of paramount importance to devise or refine the methodology of food design innovation. This study makes a significant contribution to the field of sustainable food design by combining design methodology with sociological concepts such as "Field and Habitus" to construct the "F-U-BVF" food lifestyle analysis framework. This study examines the applicability of the F-U-BVF analytical framework, exemplified by tofu, through the refinement and translation of user needs, among other methods. The objective is to guide users towards sustainable lifestyles based on a design methodology, thereby creating multiple values conducive to food sustainability. At the same time, the deconstruction of the structural relationship, process, and methodology of sustainable food design based on the F-U-BVF analytical framework is intended to break through the barriers of traditional design science. This is to provide a new systematic research paradigm for sustainable food design, as well as to provide a new perspective on the experience and interactive relationship between people and food. Finally, it is also to provide effective food design innovation solutions for relevant multi-stakeholders. This is of great significance for the development of sustainable food design.